Effect of Stress on Later-Life Health : Evidence from the Vietnam War Draft - Cawley, John; de Walque, Damien; Grossman, Daniel (World Bank, Washington, DC, 2017)
A substantial literature has examined the impact of stress during the early stages of life on later-life health. This paper contributes to that literature by examining the later-life health impact of stress during adolescence and early adulthood, using a novel proxy for stress: risk of military induction in the United States during the Vietnam War. The paper estimates that a 10 percentage point (2 standard deviation) increase in induction risk in young adulthood is associated with a 1.5 percentage point (8 percent) increase in the probability of being obese, and a 1 percentage point (10 percent) increase in the probability of being in fair or poor health later in life. These findings do not appear to be due to cohort effects; the associations exist only for men who did not serve in the war, and are not present for women or men who did serve. These findings add to the evidence on the lasting consequences of stress, and indicate that induction risk during the Vietnam War may, in certain contexts, be an invalid instrument for education or marriage, because it appears to have a direct impact on health.